2008
DOI: 10.1111/j.1440-1843.2008.01354.x
|View full text |Cite
|
Sign up to set email alerts
|

Impaired spermatogenesis by testicular sarcoidosis

Abstract: Testicular involvement by sarcoidosis is a rare condition. A 23-year-old Japanese man had asymptomatic bilateral testicular lesions, which were detected by gallium scintigram, together with lesions located bilaterally in the uvea, lungs and hilar, and mediastinal lymph nodes and unilateral supraclavicular lymph nodes. Semen analysis demonstrated severely impaired spermatogenesis. Treatment with corticosteroid dramatically improved these lesions and restored spermatogenesis. This case report suggests that testi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

2
7
0

Year Published

2009
2009
2020
2020

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(9 citation statements)
references
References 10 publications
(15 reference statements)
2
7
0
Order By: Relevance
“…Treatment was instituted with 60 mg of oral prednisone. Repeat semen analyses showed gradual improvements in sperm count (Takiguchi et al, 2008), similar to the results reported by Svetec et al (1998).…”
Section: Discussionsupporting
confidence: 88%
See 3 more Smart Citations
“…Treatment was instituted with 60 mg of oral prednisone. Repeat semen analyses showed gradual improvements in sperm count (Takiguchi et al, 2008), similar to the results reported by Svetec et al (1998).…”
Section: Discussionsupporting
confidence: 88%
“…The case of a 23‐year‐old male presenting with ophthalmic sarcoidosis and bilateral uveitis was reported by Takiguchi et al (2008). In this case, the testes were normal in size, but ultrasound identified hypoechoic lesions.…”
Section: Discussionmentioning
confidence: 93%
See 2 more Smart Citations
“…Morbidity associated with testicular sarcoidosis includes oligospermia and infertility which are thought to be secondary to the fibrosis and occlusion of the ductus epididymis. 8,28 Treatment with corticosteroids has been shown in some cases to restore spermatogenesis. 28 …”
Section: Discussionmentioning
confidence: 99%